2002
DOI: 10.1007/s00216-002-1528-z
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model and mechanism of sublation of dye-surfactant ion complexes

Abstract: A study of dye-surfactant ion complexes, bromophenol blue (BB), an anionic dye, with hexadecyl pyridium chloride (HPC) complex, and methane violet (MV), a cationic dye, with sodium docedylbenzensulfonate complex (DBS), was carried out. On the base of the complete transport mechanisms, the Langmuir adsorption and the ion complex equilibrium in aqueous phase, a mathematic model for the ion complex system is obtained with the aid of the 4th Runge-Kuta method and the Mathematic 4.0 and Matlab programs. The effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…8. The symbols can be referred to in the literature (21). The results showed that the mathematical model can describe the solvent sublation of the BG-HPC system.…”
Section: Bg Removal By Solvent Sublation 1909mentioning
confidence: 96%
See 1 more Smart Citation
“…8. The symbols can be referred to in the literature (21). The results showed that the mathematical model can describe the solvent sublation of the BG-HPC system.…”
Section: Bg Removal By Solvent Sublation 1909mentioning
confidence: 96%
“…The mathematical model of the dye-surfactant for the solvent sublation has been described in our earlier reports (21). In the experimental condition, the Y.…”
Section: Comparison Of Theoretical and Experimental Datamentioning
confidence: 99%